APLIKASI SITOGENETIKA UNTUK MENDETEKSI ABNORMALITAS KROMOSOM PADA Benign Barrett’s EPITHELIUM YANG MENGALAMI TRANSFORMASI MALIGNA - Milliana, Alvi (Department of Biology Science and Technology Faculty UIN Maulana Malik Ibrahim Malang, 2014)
Barrett’s esophagus is a metaplastic alteration of the normal distal esophageal epithelium. Barrett’s esophagus is present in 10%–20% of patients with gastroesophageal reflux disease (GERD). Its major significance is as a predisposing factor for esophageal adenocarcinoma, which carries a high mortality rate and a rapidly growing incidence in the United States. Esophageal adenocarcinoma carries a grave prognosis, with a relative 3-year survival rate of only 20% in the United States from 1995–1998. Cancer arises in BE through a multistep sequence of events initiated by chronic GERD that leads to metaplasia, dysplasia, and adenocarcinoma sequence. Primary pathogenetic changes in cancer result from balanced rearrangements of chromosome. Losses of chromosomes 4, 18, 21, and Y were the most frequent numeric changes. The chromosome arms most frequently rearranged were 1p, 3q, 11p and 22p. Evidence of chromosomal rearrangements [t(10;16) and dup (11q)] appeared during the early stages of the BEC model. After further validation, in-vivo, they may be clinically useful for diagnosis of BE, progressing to dysplasia or esophageal adenocarcinoma